Answer:
B
Step-by-step explanation:
We have the equation:
![3n-3=4n+1](https://tex.z-dn.net/?f=3n-3%3D4n%2B1)
Let's solve for n. To do so, we want to isolate it.
Let's use the subtraction property of equality to subtract 3n from both sides:
![(3n-3)-3n=(4n+1)-3n](https://tex.z-dn.net/?f=%283n-3%29-3n%3D%284n%2B1%29-3n)
The left side will cancel...
![-3=(4n+1)-3n](https://tex.z-dn.net/?f=-3%3D%284n%2B1%29-3n)
Subtract on the right:
![-3=1n+1](https://tex.z-dn.net/?f=-3%3D1n%2B1)
Remember that 1n is the same as just n. So:
![-3=n+1](https://tex.z-dn.net/?f=-3%3Dn%2B1)
Now, let's use the subtraction property of equality again to subtract 1 from both sides:
![(-3)-1=(n+1)-1](https://tex.z-dn.net/?f=%28-3%29-1%3D%28n%2B1%29-1)
The right side will cancel. Subtract on the left:
![-4=n](https://tex.z-dn.net/?f=-4%3Dn)
Symmetric property:
![n=-4](https://tex.z-dn.net/?f=n%3D-4)
So, our answer is B.
And we're done!